New Challenges in ELT (English Language Teaching): Virtual Exchange and Mobility - Russo, Michele (ESI Preprints (European Scientific Journal, ESJ), 2025)
The present study focuses on an experience of ELT through a recent virtual exchange and mobility project, called ITALengUSA. The project aimed to foster connections between Italian and American students from different universities and high schools in Italy and in the USA, with the purpose of enhancing their proficiency in Italian and English. The work begins with an analysis of the paremiological resources employed during the speaking sessions of the project, as the syntactic and prosodic features of idioms and proverbs facilitated the students’ learning process. Owing to their culture-bound nature, paremiological resources were extensively used to engage and motivate students, helping them to improve their target language through metaphors and cultural aspects (Gedik, 2024; Granger & Meunier, 2008; Russo, 2024). After investigating the learning methods used by students, including cooperative learning, scaffolding and languaging (Nicaise, 2022), the analysis dwells on the effectiveness of translanguaging (Kramsch & Hua, 2016), which involves the practice of using more than one language in conversations. Translanguaging enabled the students of the project to integrate terms from their L1 into conversations occurring in L2, allowing them to co-construct meanings with their partners through linguistic negotiation and reformulation. Considering Coonan’s (2011) concept of “international posture”, the work concludes by discussing the incorporation of cultural aspects in the speaking sessions of the programme, drawing comparisons between Americanness, associated with globalisation and multiculturalism by Italian students, and Italianness, associated with art and culture by American students. The ITALengUSA programme, which is expanding and involving an increasing number of educational institutions in Italy and in the USA, has thus paved the way for the democratisation of language learning through collaboration with native speaker students (Novak & Tucker, 2021).